2015
DOI: 10.3171/2015.1.focus14837
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of transoral approaches, endoscopic endonasal approaches, and reduction strategies for treatment of craniovertebral junction pathology: a treatment algorithm update

Abstract: The craniovertebral junction (CVJ), or the craniocervical junction (CCJ) as it is otherwise known, houses the crossroads of the CNS and is composed of the occipital bone that surrounds the foramen magnum, the atlas vertebrae, the axis vertebrae, and their associated ligaments and musculature. The musculoskeletal organization of the CVJ is unique and complex, resulting in a wide range of congenital, developmental, and acquired pathology. The refinements of the transoral approach to the CVJ by the senior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 92 publications
1
54
0
4
Order By: Relevance
“…3,15 As outlined in an excellent review on the evolution of transoral and transnasal approaches to the craniovertebral junction, Dlouhy et al suggested the use of acute cervical traction and the addition of intraoperative neuromuscular blockade and, if the pathology is still irreducible, a transnasal or transoral approach depending on if the pathology is above or below the hard palate. 4 There is some evidence that, compared with transoral routes, transnasal approaches may have fewer complication risks, including decreased risks of infection, and could permit early extubation and early feeding. 9,14,18 Our Case 1 suggests that a combined approach works better than a single approach, as a posterior decompression, fixation, and stabilization procedure had previously failed.…”
Section: Discussionmentioning
confidence: 99%
“…3,15 As outlined in an excellent review on the evolution of transoral and transnasal approaches to the craniovertebral junction, Dlouhy et al suggested the use of acute cervical traction and the addition of intraoperative neuromuscular blockade and, if the pathology is still irreducible, a transnasal or transoral approach depending on if the pathology is above or below the hard palate. 4 There is some evidence that, compared with transoral routes, transnasal approaches may have fewer complication risks, including decreased risks of infection, and could permit early extubation and early feeding. 9,14,18 Our Case 1 suggests that a combined approach works better than a single approach, as a posterior decompression, fixation, and stabilization procedure had previously failed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dlouhy et al have further modified their algorithm originally proposed at University of Iowa for addressing craniovertebral junction pathology and now include the position of the nasopharynx and oropharynx relative to the hard palate as a discriminator of the surgical approach (endonasal, transoral, or transcervical) chosen in cases with irreducible pathology. 9 In contrast to studies that evaluate surgical corridors in cadavers and mostly small adult cohorts, we indirectly assessed the impact of age on these corridors. Although the present study is an anatomical study based on advanced imaging, the variance with age and sex does suggest that the extent of the endoscopic corridors will also likely vary with these variables.…”
Section: Discussionmentioning
confidence: 99%
“…[316] Fixation across the CVJ is occasionally necessary in the face of CVJ instability that may result from trauma, syndromic anomalies, osteoarthritis, rheumatoid arthritis, Down's syndrome, neoplasm, and many other conditions. [2356171819202122]…”
Section: Discussionmentioning
confidence: 99%
“…[123456789] Rigid constructs have been shown in biomechanical studies to provide superior fixation to semi-rigid constructs. [479101112131415] Rods are contoured to connect an occipital plate and upper cervical spine screws,[479] inviting biomechanical fatigue failure of the rod.…”
Section: Introductionmentioning
confidence: 99%